2009
DOI: 10.1088/1468-6996/10/1/014609
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of chainlike cluster movement of feeble magnetic particles by induced magnetic dipole moment under high magnetic fields

Abstract: In this paper, the motion of a chainlike cluster of feeble magnetic particles induced by high magnetic field is discussed on the basis of the results of numerical simulations. The simulations were performed on glass particles with a diameter of 0.8 mm; and the viscosity, applied magnetic field and magnetic properties of the surrounding medium were changed. In addition to the magnetic field and the difference in magnetic susceptibility between the particles and the surrounding medium, the obtained results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…For the nanocomposite sample, the effect of the NPs-rich regions protruding out of the matrix ( figure 5b ) is probably following from a different surface relaxation after ultramicrotome cut, due to compositional non–uniformity in the solid film. The contrast observed in figure 5 is in agreement with the existing literature 19 20 21 . In particular, in the force gradient image of figure 5c a fine grained structure of the single magnetic NPs is detected throughout the magnetic stripes, which is not visible in the energy loss image of figure 5d .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the nanocomposite sample, the effect of the NPs-rich regions protruding out of the matrix ( figure 5b ) is probably following from a different surface relaxation after ultramicrotome cut, due to compositional non–uniformity in the solid film. The contrast observed in figure 5 is in agreement with the existing literature 19 20 21 . In particular, in the force gradient image of figure 5c a fine grained structure of the single magnetic NPs is detected throughout the magnetic stripes, which is not visible in the energy loss image of figure 5d .…”
Section: Discussionsupporting
confidence: 92%
“…The contrast observed in figure 5 is in agreement with the existing literature192021. In particular, in the force gradient image of figure 5c a fine grained structure of the single magnetic NPs is detected throughout the magnetic stripes, which is not visible in the energy loss image of figure 5d.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The force acting between the dipoles may be attractive or repulsive, depending on their mutual location and orientation (Figure 9), resulting in aggregates. The force that is attributable to the diamagnetic dipole moments is extremely small and researchers report only a few examples [98][99][100][101].…”
Section: Magnetic Dipole-dipole Interactionmentioning
confidence: 99%
“…manganese(II) chloride). [38][39][40][41][42] While the examples above required expensive and often not easily accessible superconducting magnets to generate high magnetic fields, in recent years diamagnetic repulsion has been applied on a smaller scale using conventional permanent magnets and electromagnets. Kimura et al 43,44 demonstrated the micropatterning of cells and particles suspended in aqueous paramagnetic solutions into periodic lines.…”
Section: Introductionmentioning
confidence: 99%